ANALISIS KEBUTUHAN AIR IRIGASI DAN NERACA AIR PADA BENDUNG REJOSARI KAB. JOMBANG - Faizal Apriyanto; Faradhilah Saves (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
The need for water by all living things is an inseparable need in everyday life. In the use of water, especially for rice fields, the Government of Indonesia is carrying out development efforts in the irrigation sector which aims to be directly felt by the community in meeting water needs. Therefore, there is a need for an analysis related to water availability and water demand. This research was conducted to analyze the need for irrigation water and water balance in the Rejosari weir, district. Jombang. The results of the analysis of the need for irrigation water for the Rejosari weir for each type of plant are rice obtaining a value of 28.99 l/s/ha Palawija 6.95 l/s/ha Sugarcane 9.28 l/s/ha. Meanwhile, the total water requirement at the intake is 124.93 m3/sec. analysis of the availability of irrigation water for the Rejosari weir obtained a maximum discharge value of 10.00 m3/s in February III while the minimum discharge was 1.48 m3/s in November II. The total availability of irrigation water for one year is 180.33 m3/sec. the results of the calculation of the water balance in 1 year with a cropping pattern of 10 days, obtained 23 periods of compliance with 13 periods of non-compliance. So it can be concluded that the percentage of water balance is 64% with a water availability value of 180.33 m3/sec, the water demand at the intake is 124.93 m3/sec with a difference of 55.41 m3/sec